2017
DOI: 10.1001/jamasurg.2017.0552
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Genetic Testing in Patients With Breast Cancer

Abstract: Genetic testing is a powerful tool that allows for the detection of BRCA and non-BRCA germline mutations in individuals with high risks of breast cancer, which in turn aids in the individualization of treatment. Given the magnitude of this disease, it is of great benefit for physicians, including general surgeons, to understand the indications, interpretations, and costs associated with genetic testing in patients with breast cancer. Cost is an especially important part of the genetic testing process and point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 17 publications
2
93
0
3
Order By: Relevance
“…In fact, the step‐by‐step process is able to select a shrinking number of women to be investigated by gene test analysis: this approach looks to be really cost‐effective, although a recent study comparing BRCA1, BRCA2, PALB2, RAD51C, RAD51D, and BRIP1 analysis performed in selected and unselected women, seems to prevent more BC and OC in the general population, without previous selection . However, our mutation rate is in line with other series based on different eligibility criteria for HBOC, as referred in a recent review where the BRCA1/2 mutation rate in early onset BC, triple negative BC, bilateral BC, and family history of BC is about 30% . It also means that direct criteria for the Hub evaluation represent a significant way to collect women who are potentially at risk for HBOC syndrome, avoiding a multistep process and saving time and important costs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In fact, the step‐by‐step process is able to select a shrinking number of women to be investigated by gene test analysis: this approach looks to be really cost‐effective, although a recent study comparing BRCA1, BRCA2, PALB2, RAD51C, RAD51D, and BRIP1 analysis performed in selected and unselected women, seems to prevent more BC and OC in the general population, without previous selection . However, our mutation rate is in line with other series based on different eligibility criteria for HBOC, as referred in a recent review where the BRCA1/2 mutation rate in early onset BC, triple negative BC, bilateral BC, and family history of BC is about 30% . It also means that direct criteria for the Hub evaluation represent a significant way to collect women who are potentially at risk for HBOC syndrome, avoiding a multistep process and saving time and important costs.…”
Section: Discussionsupporting
confidence: 80%
“…35 However, our mutation rate is in line with other series based on different eligibility criteria for HBOC, as referred in a recent review where the BRCA1/2 mutation rate in early onset BC, triple negative BC, bilateral BC, and family history of BC is about 30%. 36 It also means that direct criteria for the Hub evaluation represent a significant way to collect women who are potentially at risk for HBOC syndrome, avoiding a multistep process and saving time and important costs.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendation for counseling and genetic screening for BRCA1/2 pathogenic variants is mainly based on personal and family history of breast and/or ovarian cancer, young age at disease onset, male breast cancer and multiple tumors (bilateral breast cancer or breast and ovarian cancer in the same patient) . However, BRCA testing guidelines vary by region and country . In Sweden, the Swedish Breast Cancer Group BRCA1 and BRCA2 screening criteria are used .…”
Section: Introductionmentioning
confidence: 99%
“…8 However, BRCA testing guidelines vary by region and country. 9,10 In Sweden, the Swedish Breast Cancer Group BRCA1 and BRCA2 screening criteria are used. 8 A report by Nilsson et al estimated that the Swedish BRCA testing criteria has an effectiveness of only 18% and concluded that clinical genetic testing criteria for BRCA1 and BRCA2 should be critically revised.…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary breast and ovarian cancer (HBOC) accounts for 5–10% of the total breast/ovarian cancer cases, and pathogenic variants in the high‐penetrance genes BRCA1 (MIM# 113705) and BRCA2 (MIM# 600185; BRCA1/2 ) explain about 15–20% of HBOC cases (Couch, Nathanson, & Offit, ; Shiovitz & Korde, ), although this proportion varies depending on the ascertainment criteria for BRCA1/2 testing and between ethnic groups. BRCA1/2 genetic testing is generally recommended to individuals with a personal or family history of breast/ovarian cancer, with two or more family members affected, the presence of male breast cancer and/or the presence of triple‐negative breast cancer cases, among other indicative criteria (Valencia et al, ).…”
Section: Introductionmentioning
confidence: 99%